Sensitization of GSH synthesis by curcumin curtails acrolein-induced alveolar epithelial apoptosis via Keap1 cysteine conjugation: A randomized controlled trial and experimental animal model of pneumonitis - Hee Jo, Eun; Eun Moon, Ji; Han Chang, Moon; Jin Lim, Ye; Hyun Park, Jung; Hee Lee, Suk; Rae Cho, Young; Cho, Art E; Pil Pack, Seung; Kim, Hyeon-Wee; Crowley, Liana; Le, Brandy; et al. (Journal of Advanced Research, 2023)
[Display omitted] •Curcumin improves systemic inflammation in subjects residing in an air-polluted area.•Curcumin mitigates acrolein-induced pneumonitis in a preclinical animal model.•Curcumin inhibits acrolein-induced alveolar epithelial apoptosis in a ROS-dependent manner.•Curcumin increases redox sensing of Nrf2 and thus sensitizes de novo GSH synthesis.•Curcumin-Keap1 cysteine conjugation enhances redox sensing of Nrf2. Epidemiological studies have reported an association between exposures to ambient air pollution and respiratory diseases, including chronic obstructive pulmonary disease (COPD). Pneumonitis is a critical driving factor of COPD and exposure to air pollutants (e.g., acrolein) is associated with increased incidence of pneumonitis. Currently available anti-inflammatory therapies provide little benefit against respiratory diseases. To this end, we investigated the preventive role of curcumin against air pollutant-associated pneumonitis and its underlying mechanism. A total of 40 subjects was recruited from Chengdu, China which is among the top three cities in terms of respiratory mortality related to air pollution. The participants were randomly provided either placebo or curcumin supplements for 2 weeks and blood samples were collected at the baseline and at the end of the intervention to monitor systemic markers. In our follow up mechanistic study, C57BL/6 mice (n = 40) were randomly allocated into 4 groups: Control group (saline + no acrolein), Curcumin only group (curcumin + no acrolein), Acrolein only group (saline + acrolein), and Acrolein + Curcumin group (curcumin + acrolein). Curcumin was orally administered at 100 mg/kg body weight once a day for 10 days, and then the mice were subjected to nasal instillation of acrolein (5 mg/kg body weight). Twelve hours after single acrolein exposure, all mice were euthanized. Curcumin supplementation, with no noticeable adverse responses, reduced circulating pro-inflammatory cytokines in association with clinical pneumonitis as positive predictive while improving those of anti-inflammatory cytokines. In the pre-clinical study, curcumin reduced pneumonitis manifestations by suppression of intrinsic and extrinsic apoptotic signaling, which is attributed to enhanced redox sensing of Nrf2 and thus sensitized synthesis and restoration of GSH, at least in part, through curcumin-Keap1 conjugation. Our study collectively suggests that curcumin could provide an effective preventive measure against air pollutant-enhanced pneumonitis and thus COPD.